PERSONALLY-ORIENTED TEACHING TECHNOLOGIES AS THE MAIN ELEMENT OF PEDAGOGY - Khurramova Bibikhonim Dilshod kizi (PEDAGOGS, 2025)
Abstract: This article explores the foundational principles of a personality-oriented approach to teaching and examines a range of pedagogical technologies employed to support this approach. The effectiveness of these technologies in fostering critical thinking skills among students is also analyzed.